Implications for India of the May 2008 draft agricultural modalities - Gopinath, Munisamy; Laborde Debucquet, David (International Centre for Trade and Sustainable Development, 2008)
In this study, we examine the implications of the May 2008 WTO draft agricultural modalities for India’s market access and domestic support policies. In the case of market access, most of India’s agricultural tariffs are of the ad valorem kind, where the simple average of bound tariffs is 115 percent in 2004. Trade weighting increases the average bound tariff to 159 percent. However, the applied tariffs average 59 percent and hence, the binding overhang (the gap between bound and applied tariffs) is high. Our analysis focuses on the tiered tariff reduction formula and on the special and differential treatment afforded to developing countries. We assume that India will designate 7.5 percent of its HS6 tariff lines as sensitive products, and two categories of special products: about 6.5 percent of the HS6 lines face a tariff cut of 18.5 percent, and an additional 6.5 percent of the HS6 lines with a tariff cut of 11.5 percent. A selection approach based on the estimated cost of agricultural tariffs is used to identify potential special and sensitive products. The tariff-rate quotas to accompany sensitive products may be less attractive to India and hence, it may fully rely on special products. Applying the formula by bands will result in an overall cut of 38 percent in the average trade weighted bound tariffs from 159 percent to 99 percent. However, flexibilities increase the bound rates to 126 percent, resulting in a net reduction of 21 percent, well below the maximum cut of 36 percent proposed for developing countries. Although the formula reduces tariff heterogeneity, measured by the standard deviation, flexibilities restore heterogeneity to initial levels in key products sustaining potential distortions in Indian agriculture. The average applied rate would fall to 54 percent from an initial 59 percent after the formula cut, but flexibilities completely eliminate the reduction. In terms of preferences, only duty-free, quota-free access to least developed countries, if granted, would result in significant changes in India’s applied protection. In general, the formula cut with flexibilities does not appear to open India’s market and may not lead to less heterogeneity in the protection structure. India is a net agricultural exporter, but the modalities offer significant liberalization on only 30 percent of Indian exports; the ones targeting developed economies. India’s strong support of special and differential treatment opens few new market opportunities in developing countries. In the Uruguay Round, India did not have a total AMS commitment, and so, the de minimis exemptions served as limits to two types of domestic support: administered prices under product-specific AMS and input subsidies under non-product-specific AMS. Official notifications, available for 1995-1997, show negative product-specific AMS because support prices are lower than external reference prices. Moreover, a reallocation of input subsidies from non-product-specific AMS to special and differential treatment reduces the former to about 1 percent of the value of production. A recent set of shadow notifications shows that Implications for India of the May 2008 Draft Agricultural 2 Modalities India’s product-specific AMS remained negative through 2005. Non-product-specific AMS, computed similar to that in the official notifications, accounts for about 1 percent of the value of agricultural production. With India’s general elections expected in early 2009, the immediate future includes popular policies such as credit subsidies and significant MSP growth. Nevertheless, non-product-specific AMS is not likely to exceed the limits proposed in the Doha Round, i.e., 10 percent of value of production, even with popular policies. However, product-specific AMS is on the verge of becoming positive given high growth in support prices and the appreciation of Rupee in recent years. Projections for 2015 suggest that de minimis exemptions would be about $16 billion each for product-specific and non-product-specific AMS, giving India ample flexibility in domestic support policies.